Challenges of Utilizing Medical Big Data in Reproductive Health Research - Dong, Tianyu; Zhu, Min; Li, Rui; Wang, Xu (Frontiers in Reproductive Health, 2022)
In the background of the “Three-Child Policy” introduced by the Chinese government, reproductive health has become one of the most important public health issues. With the promotion of digitization management of medical care institutions for women and children in the country, there will be chances to acquire medical big data of obstetrics and pediatrics. Here the authors are presenting their opinions on the challenges of the management and utilization of reproductive big data.